Rio [videorecording (DVD)] - Saldanha, Carlos, 1965-; Hathaway, Anne, 1982-; Eisenberg, Jesse, 1983-; Clement, Jemaine; Mann, Leslie, 1972-; Lopez, George, 1961-; Foxx, Jamie (20th Century Fox Home Entertainment, 2011)
A comedy-adventure that centers on Blu, a flightless macaw who acts more human than bird. When Blu, the last of his kind, discovers there's another, and that she's a she, he embarks on an adventure to magical Rio. There he meets Jewel and a menagerie of vivid characters who help Blu fulfill his dream and learn to fly.